2016
DOI: 10.2341/15-052-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive Cementation Strategies on the Bonding of Y-TZP to Human Dentin

Abstract: This study evaluated the effects of different adhesive strategies on the adhesion of zirconia to dentin using conventional and self-adhesive cements and their corresponding adhesive resins. The occlusal parts of human molars (N=80) were sectioned, exposing the dentin. The teeth and zirconia cylinders (N=80) (diameter=3.4 mm; height=4 mm) were randomly divided into eight groups according to the factors "surface conditioning" and "cement type" (n=10 per group). One conventional cement (CC: RelyX ARC, 3M ESPE) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
(51 reference statements)
1
36
0
3
Order By: Relevance
“…However, band is unaesthetic in the anterior, which requires esthetic compared with the posterior, and may irritate the gingiva. Thus, there is a great interest in developing methods for maintaining bonded brackets directly on restoratives, and appropriate surface treatment methods have been devised [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, band is unaesthetic in the anterior, which requires esthetic compared with the posterior, and may irritate the gingiva. Thus, there is a great interest in developing methods for maintaining bonded brackets directly on restoratives, and appropriate surface treatment methods have been devised [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…As surface treatment methods become more complicated, the clinical application of these methods become more difficult, which means that finding a simple method to enhance the bond strength becomes imperative. To increase the bond strength, a variety of surface treatments [17,18,19] such as rough polishing, sandblasting with high strength particles, glass coating, acid etching, laser treatment, and primer treatments have been reported [14,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Because the bond strength of the luting material used in this study differs substantially when bonded to CoCr alloy or to dentin, use of different abutment materials might have affected this also. With regard to debonding, however, evidence from preclinical and clinical research suggests the resin/zirconia interface was the weakest link, determining the final bond strength of the abutment/restoration complex . Future FEA might provide additional insight into possible changes in stress distribution within restorations and abutments if use of different abutment materials is compared.…”
Section: Discussionmentioning
confidence: 99%
“…Bond strength significantly varied among the types of adhesive resin cements used. A number of studies have been undertaken to compare the bond strength of various resin cements to dentin 8,21,[23][24][25][26]28) . Most of these studies reported that adhesive resin cements, that require pretreatment, have higher bond strength compared to self-adhesive resin cements 23,24,26) .…”
Section: Shear Bond Strength and Post Retention Forcementioning
confidence: 99%
“…Evaluation methods for bond strength of dental materials in dentistry usually include the micro-tensile and shear bond strength test 8,[21][22][23][24][25][26] . Root dentin has lower potential for bonding with less exposure of dentinal tubules compared to coronal dentin 27) ; reagents used during root canal treatment can affect bond strength even more 13,22) .…”
Section: Shear Bond Strength and Post Retention Forcementioning
confidence: 99%